Recent perspective of herbicide: Review of demand and adoption in world agriculture (Journal of the Bangladesh Agricultural University, 2016)
The demand of herbicide in agriculture is going to be increased and its use is increasingly being adopted around the world. Many developing countries like India, China, Bangladesh are facing shortages of workers for hand weeding crop fields as millions of people are moving to urban from rural areas. In these countries, herbicides are cheaper and more readily available than labor for hand weeding. It is inevitable that, herbicide use will increase in world agriculture, not only because millions of people are leaving rural areas, creating shortages of hand weeders, but also the need to increase crop yields. Hand weeding has never been a very efficient method of weed control often performed too late and not frequently enough. In many parts of the world, herbicides are being increasingly used to replace tillage in order to improve environmental conditions. In comparison with tillage, herbicide use reduces erosion, fuel use, greenhouse gas emissions and nutrient run-off and conserves water. This review article focuses on the status of using herbicides and its adoption in global agriculture.J. Bangladesh Agril. Univ. 13(1): 19-30, June 2015